Standard Mobile Based Wireless Broadband Networks - Dukitha, M; Kavitha, D (International Journal of Computer Sciences and Engineering, 2025)
Now-a-days there is high demand for broadband mobile services. Traditional high-speed broadband solutions depend on wired technologies namely digital subscriber line (DSL).Wi-Fi and Wimax are helpful in providing any variety of property like the mounted or transportable or nomadic connectivity without the requirement of LoS (Line of Sight) of the base station. Mobile Broadband Wireless Network (MBWN) may be a versatile and economical answer for remote areas. The IEEE Wi-Fi and Wi-Max/802.16 are the most promising technologies for broadband wireless metropolitan area networks (WMANs) and these are capable of providing high throughput even on long distances with varied QoS. These technologies ensure a wireless network that enables high speed Internet access to residential, little and medium business customers, further as net access for wireless local area network hot spots and cellular base stations. These offer support to both point-to-multipoint (P2MP) and multipoint-to-multipoint (mesh) nodes and offers high speed data (voice, video) service to the customers. In this paper, we study the issues related to, benefits and deployment of these technologies.